Robin Hood : prince of thieves [videorecording (Blu-Ray)] - Robinson, James G., 1934-; Reynolds, Kevin, 1952-; Densham, Pen; Watson, John; Lewis, Richard B., 1908-1981; Rickman, Alan; Freeman, Morgan; Connery, Sean; Slater, Christian; Costner, Kevin; Mastrantonio, Mary Elizabeth (Warner Home Video, 2009)
The legendary Sherwood Forest outlaw and a 12th-century medieval world are brought to life in this spectacular epic adventure. Enhancing the fun are 12 added minutes of footage not seen in theatres.